(untitled) (Research, Society and Development, 2021)
Objectives: Identify the self-efficacy of nursing mothers regarding breastfeeding. Method: Quantitative descriptive study with 30 women breastfeeding in the mountainous region of Rio de Janeiro. Data collection took place between February 2018 and June 2019 and the Breastfeeding Self-Efficacy Scale was used, a scale based on the opinion criterion (Likert) that specifies the level of agreement in an affirmative. For each item, points were scored from 1 to 5: 1 = strongly disagree, 2 = disagree, 3 = sometimes agree, 4 = agree, 5 = strongly agree and domains with an average score of less than four were discussed. Study approved by the Research Ethics Committee of the Anna Nery School, opinion No. 2,630,264 / 2018. Results: 60% (18) of the women had low self-efficacy to breastfeed. In relation to the technical domain, the nursing mothers demonstrated difficulty in catching, controlling pain, performing the act in public places and adapting to the needs of the mother / baby and in the interpersonal domain, insecurity regarding the family support network and low concentration in the baby during feedings. The prevalence of exclusive breastfeeding was 30%. Conclusion: Knowledge of low self-efficacy items allows early detection of maternal weaknesses with regard to breastfeeding and consequently facilitates the promotion of exclusive breastfeeding for longer.